2009
DOI: 10.1016/j.ceb.2009.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Making the Auroras glow: regulation of Aurora A and B kinase function by interacting proteins

Abstract: The conserved Aurora family of protein kinases have emerged as crucial regulators of mitosis and cytokinesis. Despite their high degree of homology, Aurora A and B have very distinctive localisations and functions: Aurora A associates with the spindle poles to regulate entry into mitosis, centrosome maturation and spindle assembly; Aurora B is a member of the Chromosomal Passenger Complex (CPC) that transfers from the inner centromere in early mitosis to the spindle midzone, equatorial cortex and midbody in la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
317
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(322 citation statements)
references
References 127 publications
4
317
0
1
Order By: Relevance
“…The levels and activities of Aurora kinases are precisely modulated throughout the cell cycle via a complex network of regulatory mechanisms that involves control of mRNA synthesis and translation rates, post-translational modifications, association with specific cofactors and protein degradation 48 . Surprisingly, the contribution of mRNA decay has been largely overlooked in studies of mitosis regulation 13,49,50 .…”
Section: Discussionmentioning
confidence: 99%
“…The levels and activities of Aurora kinases are precisely modulated throughout the cell cycle via a complex network of regulatory mechanisms that involves control of mRNA synthesis and translation rates, post-translational modifications, association with specific cofactors and protein degradation 48 . Surprisingly, the contribution of mRNA decay has been largely overlooked in studies of mitosis regulation 13,49,50 .…”
Section: Discussionmentioning
confidence: 99%
“…The AurA-TPX2 complex participates in spindle assembly promoted by chromatin/RanGTP but not by centrosomes and in setting a proper spindle length (11,15,16). Although several factors have been implicated in AurA regulation at centrosomes (7,8,(17)(18)(19), the mechanism of AurA recruitment to and activation at these organelles has been unclear. Hence, the existence of a centrosome-specific AurA activator distinct from TPX2 and other known AurA cofactors has been proposed (20).…”
mentioning
confidence: 99%
“…Among the proteins that localize to centrosomes in a Cep192-dependent manner is aurora A (AurA) (4,6), a serine/threonine kinase involved in mitotic entry, centrosome maturation, bipolar spindle assembly, and cell polarity (7,8). AurA activation depends on the phosphorylation of threonine (T) 288/295 (in human/Xenopus AurA, respectively) in its kinase activation loop (9,10) and, in one specific mitotic setting, on the binding of targeting protein for Xklp2 (TPX2), a MTnucleating protein (10)(11)(12).…”
mentioning
confidence: 99%
“…Aurora kinases exert multiple roles in diverse cell cycle-related processes by phosphorylating a wide variety of substrates (Biggins and Murray, 2001;Carmena et al, 2009;Fu et al, 2009;Hans et al, 2009;Van Damme et al, 2011;Petrovská et al, 2012;Hochegger et al, 2013;Demidov et al, 2014;Goldenson and Crispino, 2015;Weimer et al, 2015). However, to date, only histone H3 (Hsu et al, 2000) and TPX2 have been reported as alpha Aurora substrates in plants (Demidov et al, 2005;Tomaštíková et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…mammals (Crane et al, 2004), Arabidopsis (Demidov et al, 2005;Van Damme et al, 2011)]. Mammalian Aurora kinases, designated A, B, and C, have very high sequence similarity, but different subcellular localization and substrate specificity (Vader and Lens, 2008;Carmena et al, 2009). Whereas both A-and B-type Auroras are expressed in proliferating cells, Aurora A is associated mainly with centrosomes and the spindle apparatus from prophase through telophase, and Aurora B is present at the kinetochores during spindle biorientation and at the midzone during anaphase and telophase.…”
mentioning
confidence: 99%